TASAWUF SEBAGAI SOLUSI BAGI PROBLEMATIKA KEMODERNAN: Studi Pemikiran Tasawuf M. Amin Syukur - Thohir, Umar Faruq (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2013)
Abstract: This article aims to elaborate Sufism thought of Amin Syukur. Hepositioned Sufismas one of the solutions to the problems of modernity who have lost the vision of divinity that result in psychological symptoms, namely spiritual emptiness. Then, the people would become stress and worry wart because of their hopless feeling. For this reason, M. Amin Syukur endorsed the problems of modernity with always optimistic, positive thinking, resting every intention and good deeds only to worship God and sharing (solidarity) for fellow creatures of God. In addition, he recommends to remember (al-Å¼ikr) to Godhowever, whenever, and wherever. Remembering God can calm the soul (sakÄ«na) and mind that will affect the nerve, the nerve will affect the glands, the glands will produce healthy liquid. Healthy liquid which is a calm soul effect which will make man have the